A retrospective study on the prevalence of dry socket in patients who attended a polyclinic for extraction - Mustafa, Nazih Shaban; Kashmola, Muhanad Ali Hamdon; Abdul Jabbar, Omar; Mustafa Al-Ahmad, Basma Ezzat (Ektodermal Displazi Grubu, 2018)
Dry socket is one of the most common post-operative complications following extraction of permanent teeth. The aetiology of dry socket is a subject of debate; it is probably multifactorial. However, its pathogenesis remains unclear. The aim of the present study was to evaluate the prevalence of dry socket following extraction of permanent teeth at Dental Polyclinic of Kulliyyah (Faculty) of Dentistry, International Islamic University Malaysia. Retrospective reviews of records of 3,452 extractions of permanent teeth for various reasons from June 2009 to July 2012, were studied. Information regarding biography of the patient, indications for extraction, extraction site (upper or lower arch), extraction technique and procedure were retrieved and analysed. There were 3,452 dental extractions carried out within the study period. The overall prevalence of dry socket was 1.13%. The prevalence of dry socket with regard to gender was 1.3% in males, and 1% in females. The peak prevalence (2.24%) was in the group of patients aged below 20 years. The prevalence of dry socket cases recorded from surgical removal of impacted teeth group was 5.8%. Data evaluation based on site of extraction showed that the prevalence in the upper jaw was less (0.98%) than that in the lower jaw (1.26%). Following surgical extractions, the prevalence of dry socket was 6.88%, while in simple extraction, the prevalence was 0.77%. These results strongly suggest that the aetiology of dry socket is multifactorial, and that the healing potential of the patient ultimately determines the severity and duration of the condition. The incidence of dry socket was higher in male patients, age group of 21 – 30 years, extractions due to caries, extraction of lower teeth, and in surgical extractions.